2020
DOI: 10.1111/jsr.13055
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to total 36‐hr sleep deprivation reduces physiological and psychological thermal strain to whole‐body uncompensable passive heat stress in young adult men

Abstract: Total sleep deprivation (TSD, sleeplessness ≥ 24 hr; Kato et al., 2000; Muginshtein-Simkovitch et al., 2015) has been reported to strongly alter control of body thermoregulation. Despite the large number of studies of this phenomenon, the clearest evidence for this effect comes from investigations of rats deprived of sleep for long periods of time (e.g., ~13 days of TSD;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Cardiac index and SVRI did not significantly change with TSD and psychological stress, consistent with prior studies (Kato et al, 2000;Lü et al, 2018). However, seated SV, HR, LVET, and BP all significantly changed with sleep loss and psychological stress as has been shown in some studies (Kato et al, 2000;Meier-Ewert et al, 2004;Zhong et al, 2005;Sauvet et al, 2010;Sunbul et al, 2014;Lü et al, 2018;Bourdillon et al, 2021;Bozer et al, 2021;Cernych et al, 2021), but not others (Kato et al, 2000;Sauvet et al, 2010;Bourdillon et al, 2021;Bozer et al, 2021). Discrepancies in study findings may be due to differences in the severity of TSD and/or stress conditions or in hemodynamic collection methods such as the angle dependency of Doppler.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Cardiac index and SVRI did not significantly change with TSD and psychological stress, consistent with prior studies (Kato et al, 2000;Lü et al, 2018). However, seated SV, HR, LVET, and BP all significantly changed with sleep loss and psychological stress as has been shown in some studies (Kato et al, 2000;Meier-Ewert et al, 2004;Zhong et al, 2005;Sauvet et al, 2010;Sunbul et al, 2014;Lü et al, 2018;Bourdillon et al, 2021;Bozer et al, 2021;Cernych et al, 2021), but not others (Kato et al, 2000;Sauvet et al, 2010;Bourdillon et al, 2021;Bozer et al, 2021). Discrepancies in study findings may be due to differences in the severity of TSD and/or stress conditions or in hemodynamic collection methods such as the angle dependency of Doppler.…”
Section: Discussionsupporting
confidence: 85%
“…During non-rapid eye movement (non-REM) sleep, HR and BP decrease from greater parasympathetic activity, while during REM sleep, there is a shift toward greater sympathetic activity; moreover, sleep loss results in less parasympathetic and greater sympathetic activity ( Kato et al, 2000 ; Henelius et al, 2014 ; Tobaldini et al, 2017 ). During TSD and SR, CV measures such as SV ( Lü et al, 2018 ), HR ( Kato et al, 2000 ; Meier-Ewert et al, 2004 ; Zhong et al, 2005 ; Sauvet et al, 2010 ; Sunbul et al, 2014 ; Lü et al, 2018 ; Bourdillon et al, 2021 ), cardiac index (CI) ( Sunbul et al, 2014 ), BP ( Kato et al, 2000 ; Muenter et al, 2000 ; Meier-Ewert et al, 2004 ; Zhong et al, 2005 ; Mullington et al, 2009 ; Sauvet et al, 2010 ; Lü et al, 2018 ; Bourdillon et al, 2021 ; Bozer et al, 2021 ; Cernych et al, 2021 ), and vascular resistance ( Kato et al, 2000 ; Lü et al, 2018 ) have shown inconsistent changes, with some studies reporting alterations, while others show no changes. To our knowledge, no prior study has examined changes in LVET during sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…These protocols for stress tests are explained in detail and have been extensively studied in previous studies (Hernando et al, 2016;Peralta et al, 2019;Cernych et al, 2021). These will be summarized in the following three subsections.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Fujita et al (2003) noted that, during a 60 min whole-body exposure to 30 • C air and while the lower legs were immersed in 42 • C water, the total sweat loss (indicated by the changes in body weight) was impaired by TSD; however, the increases in regional dry heat loss (reflected by an increase in back and forearm skin blood flow) and body T c were potentiated and diminished, respectively. In addition, after 36 h of TSD, the body T c elevation during iterative exposures to severe humidity) was dampened, despite a reduction in the whole-body sweat loss (Cernych et al, 2021).…”
Section: Thermoregulation In Response To Heatmentioning
confidence: 97%
“…With regard to the impact of PSD, relatively short periods of sleep restriction (1-4 nights; 4-5 h sleep per night) ostensibly do not impose a potent risk for thermoregulatory dysfunction during heat stress (Cernych et al, 2021;Muginshtein-Simkovitch et al, 2015;Tokizawa et al, 2015). Of note, however, is the work by Tokizawa et al (2015) showing that, although a night of PSD (4 h of sleep) did not perturb temperature regulation during morning exercise, it exacerbated the exercise-induced elevation in body T c during successive exercise bouts performed during the same afternoon (ambient conditions: 35 • C, 40% relative humidity).…”
Section: Thermoregulation In Response To Heatmentioning
confidence: 99%